Transgressive-racialization: a collective refusal of racial governance - Pérez, Jonathan (Frontiers in Education, 2025)
This analysis introduces transgressive-racialization as a praxis for resisting race’s structural imposition in U.S. schools. Drawing on Kantian notions of apperception, Althusser’s theory of interpellation, and Omi and Winant’s racial formation theory, transgressive-racialization is conceptualized as a collective refusal that unsettles the racial ontologies schools often re/produce. Extending this framework, I further develop the concepts of counterapperception and counterinterpellation to describe possibilities of internally and externally negotiating racialized logics as both imposed and inhabited. The analysis integrates insights from Trans Scholars of Color to ground transgressive-racialization in politics that refuse race’s legibility and governability. Educational institutions are positioned not as neutral transmitters of knowledge but as racializing state apparatuses in which students encounter, contest, and occasionally reconfigure the ideological scripts that define them. Transgressive-racialization emerges as a pedagogical praxis of ontological resistance. This interdisciplinary intervention contributes to ongoing conversations in race scholarship, education, and trans studies by offering educators a vocabulary for reimagining racial subjectivity beyond determinism and toward a refusal of racial governance.